Quarantine Perception during Lockdown in View of COVID – 19 - Regi Bai, R.; Mohanalakshmi, D. (International Journal of Nursing Research, 2023)
Background: Novel Coronavirus disease (COVID-19) originating from China on December 2019 has rapidly crossed borders, infecting people throughout the whole world. This phenomenon has led to a massive public reaction; the media have been reporting continuously across borders to keep all informed about the pandemic situation. A public health measure to prevent the spread of this disease is quarantine. The public has increased level of anxiety and fewer attitudes toward quarantine even though the government is focusing a lot on it. Aim: This study attempted to assess the perception of quarantine among the nursing students during the COVID-19 pandemic. Materials and Methods: A survey was conducted using a questionnaire to assess the perception of quarantine. A total of 90 samples were selected randomly as first responders to the questionnaire. The questionnaire was distributed with the use of email and whatsApp. Results: The majority of the students strongly agree or somewhat agree for the quarantine practices in four subscale of justification, sanction, burden, and safeguard. About 97% of the samples strongly agree that the public health authority needs to explain the importance of quarantine. Conclusion: During this pandemic, most of the educated people and health professionals are aware of this infection, possible preventive measures, the importance of social distancing and government initiatives were taken to limit the spread of infection.